2015
DOI: 10.33225/pec/15.64.108
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration Between General and Special Education Teachers: Developing Co-Teaching Skills in Heterogeneous Classes

Abstract: A considerable amount of research evidence suggests that collaboration between general and special education teachers is a pillar of the effective teaching for all students, including those with learning difficulties. Adopting the above position the present study aimed to present and discuss fifteen cases regarding co-teaching in the context of “parallel support”, where a special education teacher supports a learning disabled student in a mainstream classroom. Particularly, after an in-service training for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…The present study results corroborate with Chapple’s (2009) findings where teachers who received professional training before implementing co-teaching were more compatible and achieved greater communication and were much more inclusive in co-teaching sessions, thereby emphasizing the importance of training prior to implementing co-teaching lessons. This finding is also confirmed by Tzivinikou (2015), who revealed that the tension and dispute that existed among teachers in general education and special education disappeared after receiving training in co-teaching and teachers’ attitudes toward cooperative education dramatically changed after they received training. The results of this study were also in line with the findings of Abahusain and Al-Hussein (2016), in that the lack of training is one of the biggest obstacles facing general education teachers and learning difficulties.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The present study results corroborate with Chapple’s (2009) findings where teachers who received professional training before implementing co-teaching were more compatible and achieved greater communication and were much more inclusive in co-teaching sessions, thereby emphasizing the importance of training prior to implementing co-teaching lessons. This finding is also confirmed by Tzivinikou (2015), who revealed that the tension and dispute that existed among teachers in general education and special education disappeared after receiving training in co-teaching and teachers’ attitudes toward cooperative education dramatically changed after they received training. The results of this study were also in line with the findings of Abahusain and Al-Hussein (2016), in that the lack of training is one of the biggest obstacles facing general education teachers and learning difficulties.…”
Section: Discussionsupporting
confidence: 64%
“…The scale has been constructed by the author to achieve the training program outcomes used as a main intervention of the present study. The author built the scale considering the previous literature related to the co-teaching models and the surveys used in the previous studies that examined the efficacy of co-teaching to aid learning objectives (Brown, 2013; Friend, 2016; Friend & Cook, 2010; Gately & Gately, 2001; Tzivinikou, 2015; Wilson, 2006). The scale is composed of 24 statements (Appendix 1), using a multiple-choice question on a three-point Likert scale (agree, neutral, disagree).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Plauborg (2009), it was discovered that through collaborative effort, there was an improvement with teachers' teaching and learning. Additionally, a school's success is indicated through the collaboration done by the teachers (Tzivinikou, 2015).…”
Section: Insufficient Time Allottedmentioning
confidence: 99%
“…Instructional skills possessed by a teacher of Business studies may determine learning and improve learner experience in class. Howbeit, Tzivinikou (2015) argues that instructional skills of teachers of Business studies have considerably preoccupied a number of researchers for many years and confirms that learner achievement and effective learning are impacted by the skills. In this regard, Ganira, Odundo, Gatumu, and Muasya (2019) complement that instructional methods effectiveness leverages process of learning which augment learner achievement in sustaining and reinforcing sustainable development cooperation competencies.…”
Section: Introductionmentioning
confidence: 95%